Underdiagnosis of malnutrition in infants and young children in Rwanda: implications for attainment of the Millennium Development Goal to end poverty and hunger - Binagwaho Agnès; Agbonyitor Mawuena; Rukundo Alphonse; Ratnayake Niloo; Ngabo Fidel; Kayumba Josephine; Dowdle Bridget; Chopyak Elena; Smith Fawzi Mary C (BMC, 2011)
Abstract Progress towards the first Millennium Development Goal (MDG1) to end poverty and hunger has lagged behind attainment of other MDGs due to chronic poverty and worldwide inequity in access to adequate health care, food, clean water, and sanitation. Despite ongoing challenges, Rwanda has experienced economic progress and the expansion of the national public health system during the past 20 years. However, protein-energy malnutrition in children under five is still a major concern for physicians and government officials in Rwanda. Approximately 45% of children under the age of five in Rwanda suffer from chronic malnutrition, and one in four is undernourished. For years, health facilities in Rwanda have used incorrect growth references for measuring nutritional status of children despite the adoption of new standards by the World Health Organization in 2006. Under incorrect growth references used in Rwanda, a number of children under five who were severely underweight were not identified, and therefore were not treated for malnutrition, thus potentially contributing to the under five mortality rate. Given that one in ten children suffer from malnutrition worldwide, it is imperative that all countries with a burden of malnutrition adopt the most up-to-date international standards for measuring malnutrition, and that the problem is brought to the forefront of international public health initiatives. For low income countries in the process of improving economic conditions, as Rwanda is, increasing the identification and treatment of malnutrition can promote the advancement of MDG1 as well as physical and cognitive development in children, which is imperative for advancing future economic progress.